2011
DOI: 10.1038/nature09878
|View full text |Cite|
|
Sign up to set email alerts
|

Functional complementation between FADD and RIP1 in embryos and lymphocytes

Abstract: SummaryFADD is a common adaptor shared by several death-receptors (DRs) for signaling apoptosis through recruitment and activation of caspase 81-3. DRs are essential for immune homeostasis, but dispensable during embryogenesis. Surprisingly, FADD−/− mice die in utero4-5 and conditional deletion of FADD leads to impaired lymphocyte proliferation6-7. How FADD regulates embryogenesis and lymphocyte responses has been a long standing enigma. FADD could directly bind to RIP1, a serine/threonine kinase which mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
382
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(395 citation statements)
references
References 23 publications
13
382
0
Order By: Relevance
“…This is consistent with the developmental lethality, due to cardiac failure, in FADDdeficient embryos, 72 with RIP1 deficiency rescuing the embryonic lethality associated with FADD deficiency. 71 These studies support a model in which the FADD-caspase 8-c-FLIP complex negatively regulates RIP-kinase-mediated necrosis. This raises the apparent paradox of c-FLIP interacting with caspase 8 to facilitate caspase-mediated processing of RIP kinases while c-FLIP also serves to inhibit caspase 8 in the apoptotic pathway.…”
Section: Rip1 and Rip3 As Drivers Of Necroptosissupporting
confidence: 59%
“…This is consistent with the developmental lethality, due to cardiac failure, in FADDdeficient embryos, 72 with RIP1 deficiency rescuing the embryonic lethality associated with FADD deficiency. 71 These studies support a model in which the FADD-caspase 8-c-FLIP complex negatively regulates RIP-kinase-mediated necrosis. This raises the apparent paradox of c-FLIP interacting with caspase 8 to facilitate caspase-mediated processing of RIP kinases while c-FLIP also serves to inhibit caspase 8 in the apoptotic pathway.…”
Section: Rip1 and Rip3 As Drivers Of Necroptosissupporting
confidence: 59%
“…[5][6][7] Physiological function of necroptosis has been illustrated in host defense, [8][9][10][11] inflammation, [12][13][14][15][16] tissue injury, 10,17,18 and development. [19][20][21] Necroptosis can be induced by a number of different extracellular stimuli such as tumor necrosis factor (TNF). TNF stimulation leads to formation of TNF receptor 1 (TNFR1) signaling complex (named complex I), and complex II containing RIP1, TRADD, FAS-associated protein with a death domain (FADD), and caspase-8, of which the activation initiates apoptosis.…”
mentioning
confidence: 99%
“…A marked increase in T-cell numbers was also observed in RIP1-and FADD-double knockout chimaeras (Zhang et al, 2011), suggesting that a hyper-proliferative disorder can occur when components of necroptosis signalling are altered. Furthermore, the truncated splice variant of RIP3, RIP3g, has been reported to be upregulated in cancer tissues (Yang et al, 2005).…”
Section: Necrosis and Necroptosis In Cancermentioning
confidence: 95%
“…The formation of complex II initiates the cell death signal and the decision between death via apoptosis or necroptosis is determined at this step. Caspase-8-mediated cleavage of RIP1 and RIP3 will trigger the caspase cascade and induce apoptosis (Lin et al, 1999), whereas the inhibition of caspase-8 (by zVAD-fmk, CrmA or cFLIP L ) or knockout of FADD will abrogate the apoptotic signal to favour necroptosis (Holler et al, 2000;Cho et al, 2009b;Zhang et al, 2011). Recently, O'Donnell et al (2011) reported caspase-8 to also cleave CYLD, preventing the deubiquitylation of RIP1 and thereby, necroptosis.…”
Section: Tnfr1 Induction Of Necroptosismentioning
confidence: 99%
See 1 more Smart Citation